2022
DOI: 10.3389/fpsyt.2022.844578
|View full text |Cite
|
Sign up to set email alerts
|

Empathy, Theory of Mind, and Prosocial Behaviors in Autistic Children

Abstract: Background:Previous research has suggested that children with autism spectrum disorder (ASD) display fewer prosocial behaviors, and the role of empathy or Theory of Mind (ToM) in prosocial behaviors of autistic children remains unclear.MethodsData were obtained from an ongoing longitudinal study in Guangzhou, China. A total of 96 autistic children and 167 typically developing (TD) children were enrolled. Prosocial behaviors were assessed using a subscale of the Strength and Difficulties Questionnaire and Dicta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…If the limited longitudinal evidence based on parents' reports is fairly consistent in reporting low levels of general prosocial behavior and its social-emotional correlates (e.g., empathic concern, ToM) in young children with ASD, cross-sectional studies have obtained more mixed findings. For instance, in line with longitudinal findings, data obtained via parent reports mostly indicate a lower general level of prosocial behavior in children with ASD compared to those without ASD (e.g., Russell et al, 2013;Ziv et al, 2014; but see for different results, Wang et al, 2022). In a secondary data analysis of the Millenium Birth Cohort study (n >19,000), parents' report of (low) prosocial behavior was the best predictor of ASD diagnosis compared to the other SDQ subscales (Russell et al, 2013).…”
Section: Empirical Relations Of Prosocial Behavior and Empathyrelated...supporting
confidence: 55%
“…If the limited longitudinal evidence based on parents' reports is fairly consistent in reporting low levels of general prosocial behavior and its social-emotional correlates (e.g., empathic concern, ToM) in young children with ASD, cross-sectional studies have obtained more mixed findings. For instance, in line with longitudinal findings, data obtained via parent reports mostly indicate a lower general level of prosocial behavior in children with ASD compared to those without ASD (e.g., Russell et al, 2013;Ziv et al, 2014; but see for different results, Wang et al, 2022). In a secondary data analysis of the Millenium Birth Cohort study (n >19,000), parents' report of (low) prosocial behavior was the best predictor of ASD diagnosis compared to the other SDQ subscales (Russell et al, 2013).…”
Section: Empirical Relations Of Prosocial Behavior and Empathyrelated...supporting
confidence: 55%
“…These mixed results might be partly due to the reliance on diverse paradigms to measure prosocial behavior. For example, Wang et al (2022) found that ASD and non‐ASD children did not differ on parent‐rated prosocial behavior, but did behave less altruistically in a dictator game. The study's use of a behavioral game can be regarded as a methodological strength, since prosocial behavior involving real resources was directly measured and did not just involve indirect reports.…”
Section: Discussionmentioning
confidence: 99%
“…The development of ToM is delayed in children with ASD, which appears to be specific to understanding mental states and prosocial behavior. Children with ASD show milder impairments in relationship recognition or understanding the animate-inanimate distinction [ 44 , 80 , 81 , 82 ]. Some higher-functioning children with ASD do develop a first-order ToM (the ability to attribute beliefs to others) but struggle with the second-order theory of mind (the ability to attribute beliefs about beliefs), although it depends on task complexity [ 83 , 84 ].…”
Section: Theory Of Mind (Tom): a Putatively Key Mechanism For Autism ...mentioning
confidence: 99%